Flavonoid Fisetin Alleviates Ovarian Aging of Laying Chickens by Enhancing Antioxidant Capacity and Glucose Metabolic Homeostasis - Zhaoyu Yang; Jiaxuan Zhang; Qiongyu Yuan; Xinyu Wang; Weidong Zeng; Yuling Mi; Caiqiao Zhang (Antioxidants)
Oxidative stress is a crucial factor contributing to ovarian follicular atresia and an imbalance in ovarian energy metabolism in poultry, leading to decreased laying performance in aging hens. This study aimed to investigate the effects of a natural flavonoid, fisetin, on laying performance, ovarian redox status, and energy metabolism in laying chickens. The results showed that dietary fisetin supplementation improved egg production and eggshell quality in aging laying chickens, reduced follicular atresia rate, promoted ovarian cell proliferation, elevated serum estrogen and progesterone levels, restored ovarian antioxidant capacity, and improved energy metabolism. Furthermore, fisetin treatment increased the activity of antioxidant enzymes by inhibiting NF-κB signaling and COX-2 expression while promoting SIRT1 expression in the H2O2-induced small white follicle (SWF). Additionally, fisetin significantly enhanced the anti-apoptotic capacity of SWF and promoted glucose catabolism by activating the AKT and JNK signaling pathways. In summary, fisetin supplementation can alleviate ovarian oxidative stress in aging laying chickens by upregulating SIRT1 expression and inhibiting NF-κB signaling. The activation of AKT and JNK signaling pathways by fisetin contributes to the balance of energy metabolism and promotion of follicular development in the ovaries of aging laying chickens, thereby retarding ovarian aging in poultry production.